การวิเคราะห์พลังงานแสงอาทิตย์ในเขตบริเวณอำเภอเมือง จังหวัดนครราชสีมา - หนูทอง, ภราดร; ลิ้มไขแสง, วิโรจน์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2014)
บทคัดย่อ จังหวัดนครราชสีมาเป็นจังหวัดที่มีพื้นที่และประชากรจำนวนมากซึ่งมีการใช้พลังงานในปริมาณสูง จึงจำเป็นต้องหาพลังงานทดแทนโดยเฉพาะพลังงานแสงอาทิตย์ซึ่งมีศักยภาพค่อนข้างสูง งานวิจัยจึงมี วัตถุประสงค์เพื่อวิเคราะห์พลังงานแสงอาทิตย์ในเขตอำเภอเมือง จังหวัดนครราชสีมา ตั้งแต่ปี พ.ศ. 2545 - 2553 และเพื่อหาขนาดตัวเก็บรังสีอาทิตย์ที่สามารถทำอุณหภูมินํ้าได้สูงสุดสำหรับระบบทำนํ้าร้อน อีกทั้งได้พัฒนาแบบจำลองทางคณิตศาสตร์สำหรับทำนายความเข้มรังสีอาทิตย์ การศึกษาพบว่า พลังงาน แสงอาทิตย์เฉลี่ยรายเดือนอยู่ในช่วง 16.29 0.51 ถึง 20.63 0.77 MJ/m2.day โดยมีพลังงาน แสงอาทิตย์สูงสุดในเดือนเมษายนและต่ำสุดในเดือนตุลาคม หากใช้ตัวเก็บรังสีแบบแผ่นเรียบต่อแบบ อนุกรมกันจำนวน 6 ซุด (พื้นที่ตัวเก็บรังสี 12 m2) สามารถทำอุณหภมินาได้สูงสุด และจากการพัฒนาแบบจำลองทางคณิตศาสตร์ โดยใช้วิธีการแทนค่าแบบต่อเนื่องพบว่าแบบจำลองสามารถทำนายค่า พลังงานแสงอาทิตย์ได้ดี คำสำคัญ : แบบจำลองทางคณิตศาสตร์, ความเข้มรังสีอาทิตย์, ตัวเก็บรังสีแสงอาทิตย์ Abstract Nakhon Ratchasima Province has a large area and high population therefore it consumes a high energy. The renewable energy is an important energy to support the demand of region in which the solar energy has high potential in the location. Thus, the objective of this research was to analyse the solar energy in Muang district, Nakhon Ratchasima province between 2002 - 2010 and to determine the solar collector sizing based on the maximum water temperature for solar water-heating system. Moreover, the study develops the mathematical model to predict the solar intensities. It was found that the monthly solar energy varied from 16.29 0.51 to 20.63 0.77 MJ/m2-day by the maximum solar energy in April and the minimum solar energy in October. The 6 series collector (12 m2 of solar collector areas) gave the higher water temperature. The solar intensities mathematical model by using successive substitution method were found to be in good agreement between the experimental data. Keywords : Mathematical model, Solar intensity, Solar collector